1986
DOI: 10.1021/bi00359a051
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipids chiral at phosphorus: Fourier-transform infrared study on the gel-liquid crystalline transition of chiral thiophosphatidylcholine

Abstract: Fourier-transform infrared spectroscopy (FT-IR) was used to study the structural properties of Rp, Sp, and Rp + Sp isomers of 1,2-dipalmitoyl-sn-glycero-3-thiophosphocholine (DPPsC), in comparison with those of 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC). For the vibrational modes of acyl chains, isomers of DPPsC show similar temperature and phase dependence to DPPC. However, the Rp isomer of DPPsC exhibits several unique properties: the CH2 symmetric stretching band is unusually weak, the CH2 asymmetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Although sulfur substitution for oxygen is considered conservative because the van der Waals radius, P-S bond length (Liang and Allen 1987), and anionic character of parent and modified oligonucleotides are all very similar (Frey and Sammons 1985;Chang et al 1986), there are nonetheless important differences between phosphate and phosphorothioate groups, including the existence of diastereoisomers. Interestingly, these isomers can exhibit different sensitivities to nucleases.…”
Section: Discussionmentioning
confidence: 99%
“…Although sulfur substitution for oxygen is considered conservative because the van der Waals radius, P-S bond length (Liang and Allen 1987), and anionic character of parent and modified oligonucleotides are all very similar (Frey and Sammons 1985;Chang et al 1986), there are nonetheless important differences between phosphate and phosphorothioate groups, including the existence of diastereoisomers. Interestingly, these isomers can exhibit different sensitivities to nucleases.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the concentration of SG in DPPC/ SG-liposomes (7:2, 7:3.5, 7:7) on IR spectra over the 2000-800 cm -1 range is shown in Figure 6, and the frequencies of the selected absorption bands are summarized in Table 1. 21,22 Asymmetric and symmetric stretching bands of DPPC phosphate in liposomes were noticed at 1228.4 and 1086.6 cm -1 , respectively. The most dominant features in the 1350-800 cm -1 region are due to the vibrations of the phosphate moiety.…”
Section: Resultsmentioning
confidence: 95%
“…It was thereby shown that phospholipase A2 preferentially accepts (R,)-DPP,E as a substrate, whereas phospholipase C accepts (S,)-DPP,E. The chiral thiophospholipids have been used for analysis of the stereochemical course of phosphotransferase action by phospholipase D, as well as for comparative studies of their different properties in various physical states (57)(58)(59).…”
Section: Thiophospholipidsmentioning
confidence: 99%